3 The Revised Statutes, Code, and General Laws of the State of New York 3330, § 3 (Clarence F. Birdseye ed., 1890) - (:unkn) unknown (My University, 1890)
Anyone found carrying weapons is presumed to carry with intent to commit a crime.
Keywords: CARRY; CARRY - INTENT TO COMMIT CRIME